From the Ethio-Sudan border to Central Ethiopia: assimilation of the Gumuz into the Waliso Oromo - Hailu Gelana Erko; Tesema Ta’a Wayessa; Tsegaye Zeleke Tuffa (Cogent Social Sciences, 2024)
This Article explores the history of the Gumuz community, a Nilo-Saharan linguistic family who had settled in the Goro district of the Oromia regional state, central Ethiopia. They originally lived along the Ethio-Sudanese frontier; however, disputes among the communities forced them to shift to malaria-ridden territories of the Metekel and Kamashi zones of the Benishangul-Gumuz Regional State. The study investigates their history, culture, assimilation trajectory, and socioeconomic configurations. The research utilizes oral sources, review documents, and thematic dissection to probe Gumuz’s existence in the Goro district. Data accuracy is affirmed through triangulation, with ethical norms underscoring informed consent, privacy, and cultural deference. The paper seeks to highlight the Gumuz community’s experiences and inputs, thereby augmenting our grasp of the region’s multifaceted sociocultural weave. Findings indicate that the Gumuz in Goro became part of the Waliso Oromo through Moggaasaa. They initially settled in the district under Fitawrari Habte Giyorgis’s guardianship and were bestowed land within his estate’s district. Despite their incorporation into the Oromo community and their adaptation to shifting scenarios, they have preserved connections to their Benishangul Gumuz origins, culminating in a dual ethnicity within today’s Gumuz community of the Goro district.